2014
DOI: 10.1186/1471-2334-14-316
|View full text |Cite
|
Sign up to set email alerts
|

A non-synonymous polymorphism in IL-23R Gene (rs1884444) is associated with reduced risk to schistosomiasis-associated Immune Reconstitution Inflammatory Syndrome in a Kenyan population

Abstract: BackgroundHuman Immunodeficiency Virus (HIV) and Schistosomiasis co-infection is common among residents at the shores of Lake Victoria in Kenya. About 36% of this population initiating antiretroviral therapy (ART) experience Immune Reconstitution Inflammatory Syndrome (IRIS) that complicates recovery. Several IL-23R alleles have been associated with susceptibility to both autoimmune and inflammatory diseases through T-helper type 17 (TH17) cells. However, whether or not variants within the IL-23R increase susc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…fishing villages along the shores of Lake Victoria. Areas such as these could form focal-points of IRIS development, as demonstrated previously in a Kenyan cohort with ~36% of Schistosomiasis-HIV patients on ART developing worsening schistosomiasis symptoms consistent with IRIS [ 11 ]. Thus, while perhaps not as prevalent as IRIS associated with tuberculosis (TB-IRIS) [ 3 , 12 ], the clinical burden of Schisto-IRIS in the field should not be underestimated.…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations
“…fishing villages along the shores of Lake Victoria. Areas such as these could form focal-points of IRIS development, as demonstrated previously in a Kenyan cohort with ~36% of Schistosomiasis-HIV patients on ART developing worsening schistosomiasis symptoms consistent with IRIS [ 11 ]. Thus, while perhaps not as prevalent as IRIS associated with tuberculosis (TB-IRIS) [ 3 , 12 ], the clinical burden of Schisto-IRIS in the field should not be underestimated.…”
Section: Introductionmentioning
confidence: 66%
“…Patients from a prospective case-control study at the fishing community in Uyoma, Rarieda District, Kenya, were studied as described previously [ 10 , 11 ]. The study focused on a group of permanent residents that are occupationally-exposed to water infested with the infective stage of the Schistosoma mansoni parasite ( S1 Fig ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The IL-23R rs1884444T/G polymorphism is associated with various diseases. It has been reported that rs1884444 is correlated with reduced risk to schistosomiasis-associated immune reconstitution inflammatory syndrome in a Kenyan population (Ogola et al, 2014). This SNP can be found in the Chinese population as well.…”
Section: Discussionmentioning
confidence: 85%